2020
DOI: 10.1371/journal.pone.0241550
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost commercial borosilicate glass slides for passive radiation dosimetry

Abstract: For x- and gamma- irradiations delivering entrance doses from 2- up to 1000 Gy to commercial 1.0 mm thick borosilicate glass microscope slides, study has been made of their thermoluminescence yield. With an effective atomic number of 10.6 (approximating bone equivalence), photon energy dependency is apparent in the low x-ray energy range, with interplay between the photoelectric effect and attenuation. As an example, over the examined dose range, at 120 kVp the photon sensitivity has been found to be some 5× t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…However, the study itself showed a higher prevalence of COPD patients that required hospitalization (48.2% of COPD population vs. 26.5% of non-COPD population) 22 . Other studies reported a COPD prevalence of 2% in COVID-19 patients 23 . Emami and colleagues showed a COPD incidence of 0.95% in hospitalized COVID-19 patients 24 .…”
Section: Discussionmentioning
confidence: 91%
“…However, the study itself showed a higher prevalence of COPD patients that required hospitalization (48.2% of COPD population vs. 26.5% of non-COPD population) 22 . Other studies reported a COPD prevalence of 2% in COVID-19 patients 23 . Emami and colleagues showed a COPD incidence of 0.95% in hospitalized COVID-19 patients 24 .…”
Section: Discussionmentioning
confidence: 91%
“…In several materials frequently used in criminal activity, such as glass, Earth, safe insulating traces, and so forth, thermoluminescence can be an intriguing strategy. When the TL traits do not match, it is possible to confidently conclude that a specific sample did not originate from a recognised source, known as exclusionary evidence (Bradley et al, 2020;N. Itoh, 2002).…”
Section: Biology and Biochemistrymentioning
confidence: 99%